The Expanded Text of Ecclesiasticus : Its Teaching on the Future Life as a Clue to its Origin. - Kearns, Conleth (Deuterocanonical and cognate literature studies ;, 2011)
In spite of its importance for the textual history and the theological significance of the Book of Ben Sira, especially in its two different Greek versions, the 1951 doctoral thesis of Conleth Kearns has never been published and is only in circulation in photocopies. Kearns brought together a great quantity of textual and theological observations on the additions to the first Greek version concerning eschatology which are not to be found anywhere else until now. He has actually shown that these additions are part of a whole pseudepigraphic literature. That is the reason why this monograph.